Upaya Peningkatan Mobilitas Fisik Pada Pasien Post Orif Fraktur Femur Sinistra - Ihtisan, Abid Hutaful; , Fahrun Nur Rosid, S.Kep., Ns., M.Kes (2017)
Traffic accidents judged to be the third killer after heart disease coronary and tuberculosis one that occurred after a traffic accident that fractured. Fraktur is an interruption of continuity of bone or cartilage tissue that is generally caused by involuntary. One of the problems that occur in patients post ORIF (open reduction internal) femoral fracture limitation of motion of the knee joint that is experienced by the patient, the fracture can cause defects in the limbs fractured. While physical disability can be restored gradually through a range of motion 2 exercises is to practice Range Of Motion (ROM). The purpose of the author in order to understand the nursing care in patients with a diagnosis of postoperative femoral fracture sinistra. The method used is descriptive case study approach, is to perform nursing care in patients with postoperative femoral fracture ranging from assessment, intervention, implementation, and evaluation of nursing. After 3x24-hour nursing care for patients with femur fractures postoperative acute pain problems solved partially fill interventions, physical mobility impairments resolved intervention is stopped, the risk of infection is resolved and the intervention is stopped. ROM influence on the patient's postoperative femoral fracture effective to train a range of motion and prevent muscle stiffness.Ny. S case of the assessment results. There are three nursing problems are acute pain, impaired physical mobility, and the risk of infection. After nursing actions during 3x24 hours of acute pain is resolved in part, impaired physical mobility is resolved, and the risk of infection is resolved. Recommended for patients always control according to a fixed schedule and family can also make independent nursing actions at home. Keywords :Physical mobility constraints, Post ORIF, Fraktur femur, ROM.